2019
DOI: 10.1038/s41598-018-37558-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history and postglacial colonization of an Asian pit viper (Gloydius halys caucasicus) into Transcaucasia revealed by phylogenetic and phylogeographic analyses

Abstract: It has been generally acknowledged that glacial climates at the time of the Pleistocene altered the patterns of species distributions, prompting latitudinal and altitudinal distribution shifts in several species, including poikilothermic species commonly known for their thermal sensitivity. However, the historical phylogeographic patterns of such species have remained largely unknown. Here, we present the historical biogeographic, phylogenetic, and phylogeographic relationships of the Caucasian pit viper, G. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 79 publications
0
18
0
1
Order By: Relevance
“…These studies have shown that impact of climate fluctuation is more complicated and may not follow a prevailing scenario of glacial retraction and postglacial expansion as has been reported from the more northerly located regions of the western Palaearctic (Chiocchio, Bisconti, Zampiglia, Nascetti, & Canestrelli, ). Indeed, Southern Europe, Turkey, the southern parts of the Caucasus and Alborz act as multiple glacial refugia due to topographical heterogeneity and low latitude (Ahmadzadeh, Flecks, et al, ; Asadi et al, ; Rossiter, Benda, Dietz, Zhang, & Jones, ). In Iran, some species experienced range contractions to glacial refugia located, for example, in the Zagros, Alborz, and Kope Dagh Mountains, which were followed by postglacial expansion for Brandt's Persian lizard, Iranolacerta brandtii (Ahmadzadeh, Carretero, et al, ), oriental green lizards of the Lacerta trilineata (Ahmadzadeh, Flecks, et al, ), two sympatric moth species, Gnopharmia colchidari and G. kasrunensis (Rajaei Sh et al, ), Persian jird, Meriones persicus (Dianat, Darvish, Cornette, Aliabadian, & Nicolas, ), greater horseshoe bat, Rhinolophus ferrumequinum (Shahabi, Akmali, & Sharifi, ), Asian pit viper, Gloydius halys caucasicus (Asadi et al, ), and Eastern rock nuthatch, Sitta tephronota , (Yousefi, Shabani, & Azarnivand, ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that impact of climate fluctuation is more complicated and may not follow a prevailing scenario of glacial retraction and postglacial expansion as has been reported from the more northerly located regions of the western Palaearctic (Chiocchio, Bisconti, Zampiglia, Nascetti, & Canestrelli, ). Indeed, Southern Europe, Turkey, the southern parts of the Caucasus and Alborz act as multiple glacial refugia due to topographical heterogeneity and low latitude (Ahmadzadeh, Flecks, et al, ; Asadi et al, ; Rossiter, Benda, Dietz, Zhang, & Jones, ). In Iran, some species experienced range contractions to glacial refugia located, for example, in the Zagros, Alborz, and Kope Dagh Mountains, which were followed by postglacial expansion for Brandt's Persian lizard, Iranolacerta brandtii (Ahmadzadeh, Carretero, et al, ), oriental green lizards of the Lacerta trilineata (Ahmadzadeh, Flecks, et al, ), two sympatric moth species, Gnopharmia colchidari and G. kasrunensis (Rajaei Sh et al, ), Persian jird, Meriones persicus (Dianat, Darvish, Cornette, Aliabadian, & Nicolas, ), greater horseshoe bat, Rhinolophus ferrumequinum (Shahabi, Akmali, & Sharifi, ), Asian pit viper, Gloydius halys caucasicus (Asadi et al, ), and Eastern rock nuthatch, Sitta tephronota , (Yousefi, Shabani, & Azarnivand, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an exact knowledge of the biodiversity of these regions is of paramount interest for biogeography and conservation. Until today, there exist only a handful of herpetological studies using molecular genetic approaches (Asadi et al., 2019; Dufresnes et al., 2019; Macey, Wang, Ananjeva, Larson, & Papenfuss, 1998; Poyarkov et al., 2014; Shahamat, Rastegar‐Pouyani, Rastegar‐Pouyani, Hosseinian Yousefkhani, & Wink, 2020; Solovyeva et al., 2018). This is explained by the cultural and ethnic diversity and complicated political circumstances preventing broadscale research.…”
Section: Discussionmentioning
confidence: 99%
“…During the Quaternary stadials, the prevalent climate of the region was cold/dry and the species was likely sheltered in the southern refugia until interstadials when the climate became warmer and moist (Kehl, 2009). The Alborz Mountains and the southern Caspian Sea have been reported as refugia for many other species (Ahmadzadeh, Flecks, Carretero, Mozaffari, Böhme, et al, 2013;Asadi et al, 2019;Saberi-Pirooz et al, 2018;Veith et al, 2003;Zohary, 1973), acting as sources of subsequent diversifications , which eventually promoted haplotype admixture.…”
Section: Evolutionary History Of Lacerta Strigatamentioning
confidence: 99%